Pragmatic treatment of stiff person spectrum disorders - Balint, Bettina; Meinck, Hans-Michael (Movement disorders clinical practice, 2018)
Background: Stiff person spectrum disorders (SPSD) are a group of rare conditions clinically characterized by stiffness, spasms, and heightened stimulus sensitivity. They also share a spectrum of antibodies. Methods: We reviewed the literature and our own experience with the aim of providing a practical approach to the treatment of SPSD. Results: Because of the rarity of SPSD, there is little evidence to guide treatment decisions. The treatment of SPSD is based on the triad of symptomatic treatment, immunotherapy, and tumor treatment where appropriate. Moreover, the management involves continuous and appropriate monitoring of the symptoms of the disease, its autoimmune associations, and potential treatment side effects. Conclusions: Here we delineated a pragmatic treatment approach to SPSD, based on our experience and existing literature. We also highlighted how our understanding of neuronal antibodies and their implications reflects on management considerations.
Gesehen am 04.03.2020